1999
DOI: 10.1021/bi991620j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of 8-Amino-7-oxononanoate Synthase:  Spectroscopic, Kinetic, and Crystallographic Studies,

Abstract: 8-Amino-7-oxononanoate synthase (also known as 7-keto-8-aminopelargonate synthase, EC 2.3.1.47) is a pyridoxal 5'-phosphate-dependent enzyme which catalyzes the decarboxylative condensation of L-alanine with pimeloyl-CoA in a stereospecific manner to form 8(S)-amino-7-oxononanoate. This is the first committed step in biotin biosynthesis. The mechanism of Escherichia coli AONS has been investigated by spectroscopic, kinetic, and crystallographic techniques. The X-ray structure of the holoenzyme has been refined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
188
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(198 citation statements)
references
References 29 publications
9
188
1
Order By: Relevance
“…In both the glycine and succinyl-CoA soaked R. capsulatus ALAS crystals, a 15° rotation of the pyridine ring around the C5-C5A bonds occurs such that the O3 and C4A atoms move away from the catalytic lysine (10). Upon the binding of product in AONS, a similar rotation of the pyridine ring occurs along with subtle rearrangement of the active site hydrogen bond system (13). In R. capsulatus ALAS, the movement of the O3 is tracked by the residue equivalent to murine ALAS H282 (10), indicating that this residue is probably involved in coordinating the movement of the pyridine ring with the reorganization of the hydrogen bond system occurring upon substrate binding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both the glycine and succinyl-CoA soaked R. capsulatus ALAS crystals, a 15° rotation of the pyridine ring around the C5-C5A bonds occurs such that the O3 and C4A atoms move away from the catalytic lysine (10). Upon the binding of product in AONS, a similar rotation of the pyridine ring occurs along with subtle rearrangement of the active site hydrogen bond system (13). In R. capsulatus ALAS, the movement of the O3 is tracked by the residue equivalent to murine ALAS H282 (10), indicating that this residue is probably involved in coordinating the movement of the pyridine ring with the reorganization of the hydrogen bond system occurring upon substrate binding.…”
Section: Discussionmentioning
confidence: 99%
“…No studies have examined the role of this residue in any α-oxoamine synthase family member, although based on structural data alone it has been suggested that it may function as an acid catalyst during transaldimination (12,13), play a key role in positioning the PLP aromatic ring (11), or influence the pK a of the imine nitrogen (13).…”
Section: Introductionmentioning
confidence: 99%
“…1a) 7 . The x-ray structures and catalytic mechanisms of the E. coli AONS, DANS, DTBS and BS enzymes have been reported [8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…The thioester is condensed with L-alanine in an AONScatalysed reaction to begin the late stages of biotin biosynthesis 8,13 . Labelling studies using 13 C acetate provided insight into the origin of the carbon atoms of pimeloyl-CoA and biotin in E. coli 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Additional binding of PLP to the SerT domain of PigH could be shown by addition of a solution of pyridoxal phosphate to PigH. The absorption maximum of 388 nm, characteristic of the free aldehyde form of PLP, was shifted to 414 nm, typical of an aldimine linkage of PLP to an active-site lysine 8 ( Figure S3) in a 1:1 ratio. Thus, all three domains of PigH undergo post-translational modifications 9 in preparation for their assembly-line functions.…”
mentioning
confidence: 99%